Plasma EBV-DNA monitoring in Epstein-Barr virus-positive Hodgkin lymphoma patients - Spacek, Martin; Hubacek, Petr; Markova, Jana; Zajac, Miroslav; Vernerova, Zdenka; Kamaradova, Katerina; Stuchly, Jan; Kozak, Tomas (APMIS, 2011)
Epstein-Barr virus (EBV) is associated with approximately one-third of Hodgkin lymphoma (HL) cases. EBV-DNA is often present in the plasma and whole blood of EBV-associated HL patients. However, the significance of EBV-DNA monitoring is debated. In a cohort of 165 adult HL patients, EBV-DNA viral load was prospectively monitored both in the plasma and whole blood. Diagnostic tissue samples of all patients were histologically reviewed; in 72% nodular sclerosis was detected, 24% presented with mixed cellularity (MC), and 5% had other type of HL. Tissues from 150 patients were also analyzed for the presence of latent EBV infection using in situ hybridization for EBV-encoded RNA (EBER) and immunohistochemistry for latent membrane protein (LMP1). Using these methods, 29 (19%) patients were classified as EBV positive. Using real-time quantitative PCR, 22 (76%) of EBV-positive HL patients had detectable EBV-DNA in the plasma and 19 (66%) patients in whole blood prior to therapy. In the group of EBV-negative HL cases, three (2%) patients had detectable plasma EBV-DNA and 30 (25%) patients whole blood EBV-DNA before treatment. EBV-positive HL was significantly associated with EBV-DNA positivity both in the plasma and whole blood in pretreatment samples, increasing age and MC subtype. Serial analysis of plasma EBV-DNA showed that response to therapy was associated with decline in viral load. Moreover, significantly increased plasma EBV-DNA level recurred before disease relapse in one patient. Our results further suggest that the assessment of plasma EBV-DNA viral load might be of value for estimation of prognosis and follow-up of patients with EBV-positive HL.
Keywords: RNA virová; logistické modely; proteiny virové matrix; Humans; lidé středního věku; kohortové studie; In Situ Hybridization, Fluorescence; Female; Aged; mladý dospělý; dospělí; Viral Load; Hodgkin Disease; senioři; lidé; virus Epsteinův-Barrové; Immunohistochemistry; imunohistochemie; infekce virem Epsteina-Barrové; Epstein-Barr Virus Infections; Hodgkinova nemoc; Cohort Studies; virová nálož; Viral Matrix Proteins; Adult; ženské pohlaví; Male; Herpesvirus 4, Human; hybridizace in situ fluorescenční; Middle Aged; Adolescent; DNA virů; Czech Republic; Aged, 80 and over; DNA, Viral; Young Adult; RNA, Viral; senioři nad 80 let; Česká republika; mužské pohlaví; prospektivní studie; Logistic Models; mladiství; Prospective Studies